THE EFFECT OF OLIVE OIL SUPPLEMENTATION IN ADOLESENCE - Andi Faradilah; Darmawansyih; Burhanuddin Darwis (Perhimpunan Dokter Gizi Klinik Indonesia, 2021)
Background Olive oil has been shown to reduce the risk of atherosclerosis through its anti-inflammatory, antioxidant, and vasodilator effects. Olive oil contains polyphenols against the reaction of Reactive Oxygen Species. In Al Quran, Surah Al Mu'minin verse 20, it is stated that olive oil can be helpful as an appetite enhancer. This effect can occur through the role of MUFA as olive oil composition in the mechanism of the gut-brain axis where the hormone ghrelin produced by the intestine will enter the brain to induce appetite. The Adolescent period is a significant concern because this is a period of growth and development that requires adequate nutritional intake. The sustainability of appetite in adolescents is a good sign for fulfilling nutritional needs to support optimal growth and development. Objective This study aims to examine the effect of olive oil supplementation on the appetite score in adolescents. Methods The study was conducted at the Tahfizh Al Quran Zam-Zam Islamic Boarding School with 30 subjects divided into two groups: the treatment group (n = 15) and the control group (n = 15) who met the inclusion criteria. The study revealed that no difference was showed in the proportion of appetite scores in the two groups. Conclusion There is no difference of the appetite scores on the administration of olive oil in adolescents. Key words: Olive oil, food intake, appetite score, adolescents.